2021
DOI: 10.1002/ange.202010049
|View full text |Cite
|
Sign up to set email alerts
|

Probing Membrane Protein Association Using Concentration‐Dependent Number and Brightness

Abstract: We introduce concentration‐dependent number and brightness (cdN&B), a fluorescence fluctuation technique that can be implemented on a standard confocal microscope and can report on the thermodynamics of membrane protein association in the native plasma membrane. It uses transient transfection to enable measurements of oligomer size as a function of receptor concentration over a broad range, yielding the association constant. We discuss artifacts in cdN&B that are concentration‐dependent and can distort the oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The molecular brightness, defined as the ratio of the variance of the fluorescence intensity within a membrane region to the mean fluorescence intensity in this region, is known to scale with the oligomer size (24). The molecular brightness distributions of monomeric (Linker for Activation of T-cells, LAT; gray) (25, 26) and dimeric controls (TrkA in the presence of 130 nM nerve growth factor, NGF; black) (27) in 293T cells are shown in Figure 1A, along with the brightness distribution for FGFR1 in 293T cells stably expressing FGFR1-YFP (red). We found that FGFR1, in the absence of ligand (red line), exists in a monomer/dimer equilibrium, as its brightness distribution is between the distributions of LAT (monomer control) and TrkA in the presence of saturating concentration of NGF (dimer control).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular brightness, defined as the ratio of the variance of the fluorescence intensity within a membrane region to the mean fluorescence intensity in this region, is known to scale with the oligomer size (24). The molecular brightness distributions of monomeric (Linker for Activation of T-cells, LAT; gray) (25, 26) and dimeric controls (TrkA in the presence of 130 nM nerve growth factor, NGF; black) (27) in 293T cells are shown in Figure 1A, along with the brightness distribution for FGFR1 in 293T cells stably expressing FGFR1-YFP (red). We found that FGFR1, in the absence of ligand (red line), exists in a monomer/dimer equilibrium, as its brightness distribution is between the distributions of LAT (monomer control) and TrkA in the presence of saturating concentration of NGF (dimer control).…”
Section: Resultsmentioning
confidence: 99%
“…We thus measured EphA2 oligomer size in EphA2-enriched and depleted regions using Number and Brightness (N&B), which measures fluorescence fluctuations and reports on the oligomer size of a protein complex 34 . Experiments were performed in CHO cells under reversible osmotic stress, as described in 35 , where we imaged the equatorial plane of the membrane. Regions of EphA2-enrichment and EphA2-depletion were analyzed separately, yielding the oligomer size in these regions.…”
Section: Resultsmentioning
confidence: 99%
“…Data for LAT has been previously published. 35 To further investigate EphA2 interactions in EphA2-enriched and -depleted regions, we performed Förster Resonance Energy Transfer (FRET) experiments in HEK293T cells, using the Fully Quantified Spectral Imaging (FSI)-FRET method, with EphA2-mTurquoise and EphA2-eYFP as a FRET pair. 30 The cells were activated with ephrinA1-Fc and imaged with a 2-photon microscope to acquire full fluorescence emission spectra with pixel-level resolution.…”
Section: The Effect Of Lateral Epha2 Segregation On Epha2 Signalingmentioning
confidence: 99%
See 2 more Smart Citations